ANALISIS STRATEGI PENCEGAHAN PHISING STUDI KASUS PADA MEDIA SOSIAL FACEBOOK - Souhoka, Bagas Adiansyah; Fadillah, Rama Afan; Fathan, Muhammad; Meldiansah , Reza; Mutakin, Manarul Iza; Fauziyah (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Social media is a digital platform that allows users to connect and interact with each other. However, social media is also vulnerable to misuse by irresponsible parties, such as phishing. The impact of losing this personal data can be very detrimental, ranging from identity theft to financial fraud resulting in serious economic losses. This research uses a qualitative descriptive research method. This method describes and analyzes data obtained from Facebook social media. Indonesia was the most targeted country for phishing attacks in the last three months of 2023, with an average success rate of 84.3%. Phishing is a serious threat to social media users such as Facebook, causing losses such as identity theft, financial fraud, and the spread of malware. Users should be wary of suspicious links or requests for information, and social media platforms should improve security and user education. Facebook phishing modes include creating fake accounts, spreading phishing links, and using Facebook ads. Effective precautions include verifying website addresses, using an antivirus program, protecting your personal information, and enabling two-factor authentication. Research shows that phishing attacks are rising, with Indonesia being the main target. A joint effort between users and social media platforms is essential to create a safer digital environment.